2011
DOI: 10.4047/jap.2011.3.3.152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the immobilization of heparin and rhPDGF-BB to titanium surfaces for the enhancement of osteoblastic functions and anti-inflammation

Abstract: PURPOSEThis study was to investigate the effects of recombinant human platelet-derived growth factor (rhPDGF-BB) and heparin to titanium surfaces for enhancement of osteoblastic functions and inhibition of inflammation activity.MATERIALS AND METHODSThe anodized titanium discs, not coated with any material, were used as a control group. In heparinized- Ti group, dopamine was anchored to the surface of Ti substrates, and coated with heparin. In PDGF-Ti group, rhPDGF-BB was immobilized onto heparinized Ti surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Indeed, we confirmed that LF was successfully immobilized on the surface of Hep-Ti substrates and that the amount of LF immobilized increased with increasing feed amounts of LF. As reported in previous in vitro release studies, Hep-Ti substrates effectively prevented high initial burst effects and also showed sustained and extended release of LF for 28 days [16,41,42]. Furthermore, all Ti substrates examined in this study were non-toxic to MG-63 cells, indicating that they are safe to use.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, we confirmed that LF was successfully immobilized on the surface of Hep-Ti substrates and that the amount of LF immobilized increased with increasing feed amounts of LF. As reported in previous in vitro release studies, Hep-Ti substrates effectively prevented high initial burst effects and also showed sustained and extended release of LF for 28 days [16,41,42]. Furthermore, all Ti substrates examined in this study were non-toxic to MG-63 cells, indicating that they are safe to use.…”
Section: Discussionsupporting
confidence: 63%
“…The obtained heparinized Ti (Hep‐Ti) substrate was carefully washed with distilled water and dried under a flow of nitrogen gas. The immobilized amount of heparin to aminated Ti substrate was determined by the toluidine blue method, as previously described (Huh et al ., ; Kim et al ., ). Hep‐Ti substrate was placed in 1 ml PBS buffer, pH 7.4, containing 1 ml 0.005% toluidine blue solution.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate bone tissue response to implants, various growth factor delivery systems have been developed by modifying and functionalizing the implant surface with collagen gels, sponges, hyaluronic acid, dextran, chitosan and fibrin scaffolds for prolonged local release of growth factors (Chua et al ., ; Kim et al ., ; King et al ., ; Lee et al ., ; Shi et al ., ; Zellin and Linde, ). In our previous studies, we developed a heparinized titanium (Hep‐Ti) implant to deliver growth factors (Huh et al ., ; Kim et al ., ) because heparin has high binding affinity with growth factors (Sasisekharan et al ., ). This Hep‐Ti implant prevented the high initial burst effects of growth factors, and demonstrated the sustained and extended release rate (Huh et al ., ; Kim et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations